2019
DOI: 10.9734/ejmp/2019/v27i330116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant, Anti-inflammatory and Analgesic Activities of Leaves of Saba senegalensis (A.DC) Pichon (Apocynaceae)

Abstract: Aims: To evaluate antioxidant, anti-inflammatory and analgesic activities of extracts of Saba senegalensis leaves. Study Design: In vitro antioxidant assay and in vivo anti-inflammatory, analgesic assay of Saba senegalensis extracts. Place and Duration of Study: Saba senegalensis leaves, were collected in the Centre Region of Burkina Faso, in June–July 2015. The experiments were conducted at the department of Medicine and Traditional Pharmacopeia-Pharmacy (MEPHATRA-PH) of Institute of Research in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The CuO-NPs studied in the CFA-induced monoarthritis resulted in substantially decreased paw volume in comparison to the control . Phenolic and terpenoid chemicals are known to possess anti-inflammatory properties, and this may explain the anti-inflammatory effects in these experiences . Based on findings obtained via the leukocyte migration test, it seems that the mechanism of action of NPs involves altering the migration of leukocytes into the tissues and target organs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CuO-NPs studied in the CFA-induced monoarthritis resulted in substantially decreased paw volume in comparison to the control . Phenolic and terpenoid chemicals are known to possess anti-inflammatory properties, and this may explain the anti-inflammatory effects in these experiences . Based on findings obtained via the leukocyte migration test, it seems that the mechanism of action of NPs involves altering the migration of leukocytes into the tissues and target organs .…”
Section: Resultsmentioning
confidence: 99%
“…61 Phenolic and terpenoid chemicals are known to possess anti-inflammatory properties, and this may explain the anti-inflammatory effects in these experiences. 62 Based on findings obtained via the leukocyte migration test, it seems that the mechanism of action of NPs involves altering the migration of leukocytes into the tissues and target organs. 63 Adjuvant arthritis is utilized widely in etiology research as well as to evaluate novel natural treatments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this study, the hydroethanolic extract (IC 50 = 35.61 µg/ml) S. senegalensis showed good antioxidant activity and the aqueous extract (IC 50 = 69.57 µg/ml) had moderate activity. Belemlilga et al (2019) obtained a contrary result in their study, but the DCM fraction of the hydroethanolic extract presented the highest reducing power with a concentration of 88.88 mmol TE/g. Studies have shown that the polyphenolic compounds in the extracts may be good electron and hydrogen atom donors, and thus able to stop radical chain reactions by converting free radicals into more stable products (Amarowicz et al, 2004;Shettar et al, 2015).…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 83%
“…Previously, similar results showed, strong antiradical activity with T. macroptera, X. americana, C. tinctorium and S. senegalensis were reported. [20][21][22][23]…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 99%